2021
DOI: 10.1186/s13071-021-04972-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497 induced by Clonorchis sinensis enhances the TGF-β/Smad signaling pathway to promote hepatic fibrosis by targeting Smad7

Abstract: Background Various stimuli, including Clonorchis sinensis infection, can cause liver fibrosis. Liver fibrosis is characterized by the activation of hepatic stellate cells (HSCs) with massive production of extracellular matrix (ECM). Our previous study showed that the TGF-β1-induced Smad signaling pathway played a critical role in the activation of HSCs during liver fibrosis induced by worm infection; however, the mechanisms that modulate the TGF-β/Smad signaling pathway are still poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Smad2 and Smad3 mainly promote HF, while Smad7 inhibits TGF-β1 signaling, thereby inhibiting HF ( 39 ). Specifically, Smad7 is a negative regulatory protein participating in the TGF-β/Smad signaling pathway, which acts in a competitive fashion against TGF-βRI to prevent phosphorylation of Smad2/3, thus inhibiting the activation of the TGF-β/Smad cascade ( 40 ). The present study demonstrated that, compared with the NASH-F group, TIIA markedly reduced α-SMA mRNA and protein expression in the rat liver tissue, indicating that TIIA could inhibit the activation of HSCs and reduce the synthesis of ECM, thereby preventing the development of NASH-F.…”
Section: Discussionmentioning
confidence: 99%
“…Smad2 and Smad3 mainly promote HF, while Smad7 inhibits TGF-β1 signaling, thereby inhibiting HF ( 39 ). Specifically, Smad7 is a negative regulatory protein participating in the TGF-β/Smad signaling pathway, which acts in a competitive fashion against TGF-βRI to prevent phosphorylation of Smad2/3, thus inhibiting the activation of the TGF-β/Smad cascade ( 40 ). The present study demonstrated that, compared with the NASH-F group, TIIA markedly reduced α-SMA mRNA and protein expression in the rat liver tissue, indicating that TIIA could inhibit the activation of HSCs and reduce the synthesis of ECM, thereby preventing the development of NASH-F.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression level of TGF-β1 was measured based on previous studies [ 35 , 36 ]. Total RNA was extracted from HaCaT cells by using an RNA Extraction Kit (Tiangen, China).…”
Section: Methodsmentioning
confidence: 99%
“…TGF-β1 induces transcription, processing and maturation of pri-miR-21 through a Smad3-dependent pathway, while mature miR-21 promotes the development of fibrosis by targeting the inhibitory Smad gene-small mothers against decapentaplegic7[ 15 ]. Clonorchis sinensis promotes hepatic fibrosis by inducing miR-497 and activating the TGF-β/Smad pathway[ 17 ]. Pan et al [ 18 ] revealed that miR-16 plays an essential role in the phenotypic remodeling of myofibroblasts.…”
Section: Ncrnas In the Pathogenesis And Progression Of Liver Fibrosismentioning
confidence: 99%